The Efforts of the Kamsel Unit through Mobile Enlightenment to Prevent Traffic Accidents at Batang District. - Christopher Pasule (Advances in Police Science Research Journal, 2022)
The increasing number of motorized vehicles from year to year causes traffic problems, one of which is traffic accidents. Prevention of traffic accidents by the Police, especially in Batang District is carried out by the Kamsel Unit Batang Police Department through Mobile Enlightenment activities. In this final project, we will discuss the implementation of Mobile Enlightenment activities by the Kamsel Unit, what factors affect its implementation and the efforts made to improve the implementation of Mobile Enlightenment activities in order to prevent traffic accidents. The research was conducted using qualitative methods with data collection techniques using interviews, observation and document studies. Mobile Enlightenment is one of the activities of the Traffic Education which aims to provide an appeal to the public in maintaining traffic safety. The implementation of the Mobile Enlightenment is based on the Indonesian National Police Chief's Instructions Number: Juklak/05/V/2003 with Management theory by George Terry and Communication Theory by Harold Lasswell as analytical tools. Mobile Enlightenment by the Kamsel Unit has not been carried out optimally. In the planning, important material has not been made, and briefing by Kamsel Unit’s Chief has not been implemented prior to the implementation of the activity. there are several factors that affect the implementation of the important such as limited personnel, budget, and inadequate infrastructure. The Kamsel unit has made efforts to improve the implementation of Mobile Enlightenment but there are still some shortcomings. Based on the results of the study, the authors analyzed the comparison between the implementation of Mobile Enlightenment by the Unit Kamsel Batang Police Department with the proper Standard Operating Procedure (SOP) and found that there were still some discrepancies. Therefore, the author provides several solutions to problems such as carrying out Mobile Enlightenment during patrols and distributing brochures during Mobile Enlightenment.